Assessment of Natural Additives Modified Lime Mortars for Repair of Historic Structures with Strength, Durability and Microstructural Parameters - James, Chippymol; Sivasankarapillai, Greeshma (Periodica Polytechnica Civil Engineering, 2023)
The contemporary building material despite the significance of cement in construction industry is the lime mortars because of its usage as a structural repair material around the ancient heritage structures. Though the significance of lime mortars lies in the fact of compatibility towards the existing ancient lime-based structures, the method of construction and material preparations are still undisclosed. In such a case, it is necessary for the researchers to analyze scientifically, the influences of various additives towards the performance of lime mortars. This paper tries to attempt two natural additives viz., gallnut (Terminalia chebula) and palm jaggery (Saccharam officinarum) as modifiers of mixing water in the preparation of class B hydraulic lime-based mortars through the process of fermentation. Based upon the trials, 39 mixes were considered with varying water to lime ratios and dosages of additives. Experimental tests such as workability, compressive strength, water absorption, acid resistance and NaCl cyclic tests were conducted along with SEM and XRD microstructural assessments. The maximum compressive strength achieved was about 4.3 MPa which is 200% that of conventional lime mortars. Jaggery and gallnut-based additives were efficient in various durability studies however the performance of jaggery is superior to gallnut in various aspects.